The Effects of Dry Needling on Knee Outcomes: A Systematic Review - Hess, Kylie; Luke, Adam; Beasley, Callie; Hill, Matthew; Clewley, Derek; Oberle, Nicholas (2018)
The purpose of this systematic review was to evaluate the effectiveness of dry needling on primarily knee pain, in addition to other secondary outcomes such as function, disability, strength, & range of motion (ROM).